2021
DOI: 10.1097/md.0000000000025133
|View full text |Cite
|
Sign up to set email alerts
|

The mediating role of patient satisfaction and perceived quality of healthcare in the emergency department

Abstract: The purpose of this research was to identify whether a certain set of drivers of satisfaction/perceived quality of healthcare (PQHC) could indirectly affect patients’ confidence/trust in the emergency department (ED). Patients were seen at an ED in the public hospital in Lisbon, Portugal between January and December 2016. Data were collected between May and November 2017, using a questionnaire, by mail or e-mail. The total sample size comprised 382 patients. The data analysis included structural eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
1
4
0
1
Order By: Relevance
“…Long waiting time can significantly increase costs and be a major determinant of the satisfaction of those seeking health care services [ 1 ]. Patient experience and satisfaction are closely linked to the quality of care that users attribute to health care [ 2 , 3 ]. Although quality of care does not necessarily translate into patient satisfaction, it can be a major predictor [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Long waiting time can significantly increase costs and be a major determinant of the satisfaction of those seeking health care services [ 1 ]. Patient experience and satisfaction are closely linked to the quality of care that users attribute to health care [ 2 , 3 ]. Although quality of care does not necessarily translate into patient satisfaction, it can be a major predictor [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…As many international studies [ 8 , 30 , 36 , 37 , 41 ] show alongside this contribution, a number of factors may influence the quality assessment of the provision (as a process) of healthcare services. These factors may also have different effects on the overall assessment of HQ or on the performance of a particular facility, due to the relevance of each factor being perceived differently by each individual.…”
Section: Discussionmentioning
confidence: 97%
“…Studies evaluating patient satisfaction in emergency departments have shown patient waiting times before seeing the doctor to be an important factor in satisfaction, while prolonged times reduce satisfaction (17,18). Grissom et al reported that the number of patients and the patient waiting times in the emergency department was lower during the pandemic than in the pre-pandemic period, and that patient satisfaction increased accordingly (15).…”
Section: Discussionmentioning
confidence: 99%